Variantes en el número de copias (CNVs) y su asociación con entidades metabólicas en población amerindia mexicana - Moreno Entzin, Diana Cristina (Universidad Autónoma Metropolitana, 2021)
Metabolic diseases are those which affect the metabolism in a direct manner. Both obesity and hypertension are a major concern in public health due to its high prevalence in Mexico, said prevalence being calculated to be a 34.6% which suffer from obesity and 44.9% hypertension. The etiology of both diseases is multifactorial; however, the genetic factor has a considerable influence in the development of metabolic diseases. Within the human genome there are many types of variants, such as, SNVs (single nucleotide variations) or CNVs (copy number variations). CNVs are segments of ≥50kb, they can be gains or losses that are present throughout the human genome. However, evidence suggests CNVs are associated with the risk or protection to have obesity and hypertension. The aim of this work was to find three different CNVs (esv3586400, esv27061 and esv2758781) in Mexican Amerindians in order to investigate their association for risk or protection with obesity and/or hypertension. We found that 99% (n=200) of our population had 2 copies in the CNV esv3586400 (regions that covers the NEGR1 gene) and 1% presented losses (n=2). The relative copies analysis showed that the median of relative copies in people with hypertension and high systolic/diastolic blood pressure was significantly higher (p=0.008, p=0.007, p=0.01, respectively); consequently, we suggest that CNV esv3586400 might play a role in HTA develop. In the case of the CNV esv2706 (a region that covers the genes: LRP8, CAPZA1, CTTNBP2NL, DKFZp547A023, MOV10, RHOC, ST7L, WNT2B). We found that 99% (n=201) of our population had 2CNVs in this region, while 1% (n=1) presented duplications (3CNVs). Finally, we found that 92% (n=122) of the Mexican Amerindians had 2 copies in the CNV esv2758781 (regions that covers the genes: AL050403.2, AL158042.1, C20orf18) and 8% (n=10) presented gains. One major observation in this study was the relationship of lower median body mass index (BMI) with no hypertension and duplications as compared with individuals who presented 2 copies of this CNV (21.81kg/m2 vs 28.02 kg/m2, p=0.02). These results suggest this variant might be associated with the protection for obesity. Based on the obtained results, we suggest that the CNV esv3586400 is related with the raise of blood pressure, the CNV esv27061 does not show association in either obesity or hypertension and the CNV esv2758781 has a protector effect in obesity. These results clearly indicate the association of CNVs and metabolic disease in Mexican population. Further studies are needed to elucidate the role of this CNVs in the etiology of metabolic diseases in Mexican population.; Las entidades metabólicas (EM), son aquellas que afectan directamente el metabolismo. Tanto la obesidad (OB), como la hipertensión (HTA) son graves problemas de salud pública, ya que, en México, la OB tiene una prevalencia de mayor al 34% y de HTA del 44.9%. La etiología de ambas enfermedades es multifactorial, sin embargo, el factor genético tiene un gran peso para el desarrollo de EM. Dentro del genoma humano tenemos variaciones, estas pueden ser de un solo nucleótido (SNVs) o variantes en el número de copias (CNVs). Las CNVs son segmentos de ≥50pb, se presentan tanto como ganancias o como pérdidas, están presentes en todas las personas, no obstante, se ha evidenciado que algunas están asociadas al riesgo o protección a padecer OB e HTA. En este trabajo se buscó identificar a CNVs (esv3586400 (región que abarca al gen NEGR1), esv27061 (región que contiene a los genes LRP8, CAPZA1, CTTNBP2NL, DKFZp547A023, MOV10, RHOC, ST7L, WNT2B, SnoU13, MIR4256) y esv2758781 (región que abarca a los genes AL050403.2, AL158042.1, C20orf187)) en amerindios mexicanos y establecer su asociación al riesgo/protección de desarrollar OB o HTA. Se encontró que 99.01% (n=200) de los individuos presentó 2 copias en la CNV esv3586400 (región que abarca el gen NEGR1) y 0.99% deleciones (n=2). El análisis de copias relativas evidenció que la mediana de copias relativas en los individuos con HTA y TA sistólica/diastólica elevada, fue significativamente más elevada (p=0.008, p=0.007, p=0.01, respectivamente), por lo que se sugiere que esta CNV puede jugar un papel en el desarrollo de HTA. En el caso de la CNV esv27061 (en los genes: LRP8, CAPZA1, CTTNBP2NL, DKFZp547A023, MOV10, RHOC, ST7L, WNT2B) se encontró que 99.5% (n=201) de la población presentó 2 CNVs en esta región, mientras que 0.5% (n=1) presentó 3CNVs, no se encontró evidencia de que esta región pudiera ser de riesgo o protección a desarrollar OB o HTA. Por último, se observó que el 92.42% (n=122) de la población presentó 2 copias en la CNV esv2758781 (que abarca los genes: AL050403.2, AL158042.1, C20orf18) y 7.57% (n=10) duplicaciones. En este estudio se encontró que los individuos sin HTA y con duplicaciones en esta región presentaron una mediana más baja de Índice de Masa Corporal (IMC) que los individuos con 2 copias (21.81kg/m2 vs 28.02 kg/m2, p=0.02), lo que sugiere que esta región pueda asociarse a la protección de OB. Con base a los resultados obtenidos, sugerimos que la CNV esv3586400 podría estar relacionada con el aumento de la TA, la CNV esv27061 no tiene efecto ni en el fenotipo de SP/OB ni en el de HTA en la población amerindia mexicana y la CNV esv2758781 tiene una relación protectora a OB, por lo que se sugiere a seguir estudiando el papel que ejercen las CNVs en la etiología de EM en la población mexicana.